Rancang Bangun Sistem Informasi Pendaftaran Pernikahan Pada KUA Kecamatan Pamulang Berbasis Web - Herly Nurrahmi; Muhammad Hilmy Arief (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The development of information technology takes place rapidly, it is also happening in our beloved country. However, technological growth itself does not always coincide with the maximum application of technology. Lack of application knowledge is the main reason the problem occurs. The same thing also happened to the Office of Religious Affairs in Pamulang District. The Office of Religious Affairs in Pamulang Subdistrict is one of the agencies that uses less technology in terms of the registration process. Where people who want to register for marriage must register manually by going to the office and filling in the registration form and completing the marriage requirement documents. This is a problem because the Covid-19 pandemic has spread widely, knowing that marriage registration is not optimal. The system development method used is the Extreme Programming method. Therefore, a system has been developed that can assist the process and provide information about marriage registration. The system that will be created is designed to help people carry out web-based marriage registration. Through the development of this system, it is hoped that it can serve marriage registration activities to make it faster and easier. Keyword : Information System,Registration,Website